Rechargeable internal pulse generators as initial neurostimulators for deep brain stimulation in patients with movement disorders - Jakobs, Martin; Kloss, Manja; Unterberg, Andreas; Kiening, Karl (Neuromodulation, 2018)
Introduction Rechargeable internal pulse generators (r-IPGs) for deep brain stimulation (DBS) promise a longer battery life and cost effectiveness compared to non-rechargeable IPGs. However, patients need to learn to check the battery capacity and perform the recharging process to ensure continuous therapy. Methods n = 35 consecutive adult patients with movement disorders that underwent DBS electrode placement with implantation of a r-IPG were assessed with a questionnaire. They were asked to report on their recharging routine, user confidence, satisfaction, and adverse events. Patients were asked to assess the level of difficulty of the individual steps and the overall recharging process on an ordinal scale awarding 1-5 points. Results 89% (n = 31) patients responded and were available for data analysis. n = 21 patients received DBS for Parkinson's Disease, n = 8 for essential tremor and n = 2 for dystonia at a mean age of 63.3 years. The mean follow-up was 21.2 months. n = 7 patients have partners or nursing services check and recharge the IPG. The recharging takes an average of 57.6 min. 90.3% felt confident using their IPG after a mean of 2.1 weeks and 1.6 training sessions. 97% of patients prefer their r-IPG over a conventional one. n = 3 patients experienced inability to recharge their IPG at some point. One patient experienced battery depletion and interruption of stimulation because of inability to recharge. The overall recharging process was rated as “easy” with a score of 4.0 out of 5 points. Each individual step was also rated as “easy” with a median score of 4.0 out of 5. Old age was not associated with more adverse events or a lower rating for the recharging process. Conclusions Choosing a r-IPG during initial DBS surgery is safe and associated with a low number of adverse events even in older patients. The vast majority of patients consider handling and recharging the IPG as “easy.” Most of the patients undergoing DBS for movement disorders will benefit from the advantages of r-IPGs.